2018
DOI: 10.1002/adhm.201801036
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Cancer Theranosis Using Hyaluronate‐Conjugated Molybdenum Disulfide

Abstract: Among various 2D nanomaterials, molybdenum disulfide (MoS2) exhibits unique visible photoluminescence with high absorption at the near‐infrared (NIR) range. Despite these optical properties, the efforts to use MoS2 nanomaterials for optical imaging and photothermal therapy are hampered by their instability and low intracellular delivery efficiency. Multifunctional MoS2 conjugated with hyaluronate (HA) for cancer theranosis is reported herein. HA facilitates the delivery of MoS2 to tumor cells by the HA‐recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…The HA-NP hybrid systems have been used for biomedical applications to bioimaging, phototherapy, photomedicine, and drug delivery . For example, Lee et al developed gold nanoparticles (AuNPs) modified with thiolated low molecular weight HA (12 kDa) by chemical conjugation and with IFNα by physical binding .…”
Section: Ha-based Medicinesmentioning
confidence: 99%
“…The HA-NP hybrid systems have been used for biomedical applications to bioimaging, phototherapy, photomedicine, and drug delivery . For example, Lee et al developed gold nanoparticles (AuNPs) modified with thiolated low molecular weight HA (12 kDa) by chemical conjugation and with IFNα by physical binding .…”
Section: Ha-based Medicinesmentioning
confidence: 99%
“…Enhancing the tumor targeting of multifunctional nanomaterials can reduce the side effects on normal tissues. Shin et al [ 293 ] reported a multifunctional HA-MoS 2 with the tumor-targeting capability as well as integrated fluorescence imaging, PAT, and PTT. Thiolated HA (HA-SH) was first prepared by chemically modification of hyaluronate (HA) with cystamine.…”
Section: Multifunctional Nanoplatforms For Cancer Therapymentioning
confidence: 99%
“…[94][95][96] Nanomaterials with a photothermal effects are widely used to enhance PTT and have achieved encouraging therapeutic results. 97 Photothermal agents mainly include gold nanomaterials, like GNShs, GNRs, GNCs, GNSs; 39-50 carbon nanomaterials such as SWCNTs, graphene, fullerene, 51-56,98-100 semiconductor nanomaterials such as MoS 2 , WS 2 , Bi 2 Se 3 ; [60][61][62][101][102][103][104] organic NIR dyes such as IGC, IR780, IR820 ( Figure 1B). [63][64][65][66][67][68][69][70][71][72][73][74] However, there are still some ambiguity in PTT.…”
Section: Nanomaterial-based Ptt For Tumor Treatmentmentioning
confidence: 99%
“…Interestingly, recent revisions have shown that hyperthermia can induce dying tumor cells to release antigens, pro-inflammatory cytokines, and immunogenic intracellular substrates, thus promoting immune activation. Nanomaterials with a photothermal effects are widely used to enhance PTT, including gold nanoparticles such as gold nanoshells (GNShs), 39-41 gold nanorods (GNRs), [42][43][44] gold nanocages (GNCs), [45][46][47] gold nanostars (GNSs), 48-50 carbon nanomaterials, such as single-walled carbon nanotubes (SWCNTs), [51][52][53] graphene; [54][55][56] semiconductor nanoparticles, such as copper sulfide (CuS), [57][58][59] molybdenum disulfide (MoS 2 ) [60][61][62] organic NIR dyes such as indocyanine green (IGC), [63][64][65][66][67][68] IR780, 69-71 IR820 [72][73][74] as well as other PTT nanomaterials. In addition to direct killing effect, it is recognized that a key role caused by PTT is immunogenic cell death (ICD).…”
Section: Introductionmentioning
confidence: 99%